2014
DOI: 10.17265/2328-2169/2014.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Women in Hotel Management and Leadership: Diamond or Glass?

Abstract: Although the hospitality industry shows growth, only few women are found in high managerial positions. The hotel sector is dominated by women with an average 55.5% of the workforce, but is managed by men, as women are mainly found in positions that are stereotypically ascribed to their gender, such as directors of sales, housekeeping, and marketing. Fifteen male and 15 female managers in 5-star hotels in Greece were interviewed to explore their management and leadership styles, as well as any challenges they f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(31 reference statements)
1
6
0
Order By: Relevance
“…Similar results, which imply a clear under-representation of women on the boards of tourism companies, have already been reported by Barrientos-Báez et al [133] and Uyar et al [24]. One possible reason for this finding is that women's career development in the tourism sector is limited, with women finding it difficult to access management positions [16].…”
Section: Description Of the Samplesupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results, which imply a clear under-representation of women on the boards of tourism companies, have already been reported by Barrientos-Báez et al [133] and Uyar et al [24]. One possible reason for this finding is that women's career development in the tourism sector is limited, with women finding it difficult to access management positions [16].…”
Section: Description Of the Samplesupporting
confidence: 84%
“…From a social perspective, the potential of the tourism sector to create employment [3] means that it can contribute to meeting SDG 5 (Gender Equality), which aims to achieve gender equality and empower women and girls [1] through decent work opportunities for women [14]. At the management level, although the glass ceiling that prevents women from climbing the corporate ladder has weakened in recent decades [15] and a higher proportion of women now occupy management positions [16], women still face difficulties in their career development in the tourism sector. This situation highlights the need to address this issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, the industry is overwhelmingly managed and led by male employees. In fact, female employees are most often found working in roles in the hospitality industry that are stereotyped as 'female' including director of sales, housekeeping, and marketing (Marinakou, 2014). Additionally, hospitality scholars have shown that women are overwhelmingly selected for roles within the hotel without leadership potential.…”
Section: Female Leadership In the Hotel Industrymentioning
confidence: 99%
“…Hotel patrons are often greeted at the front desk by women, at various service points by women, and have their rooms tended to by women. Scholars have highlighted that women comprise the majority of the workforce in the hotel industry at 55.5% (Marinakou, 2014). However, the industry is overwhelmingly managed and led by male employees.…”
Section: Female Leadership In the Hotel Industrymentioning
confidence: 99%
“…A consequence of the food and masculinity paradigm and the cultural context, gender job discrimination, occurs in hospitality and professional kitchens and is discussed as a central topic in 21 journal articles, some of which deal with discrimination in general (Burrel et al, 1997;Campos-Soria et al, 2011;Carvalho et al, 2014;Jeffrey et al, 2018). Other authors have outlined it considering professional kitchen occupations in the hospitality industry (Burrell et al, 1997;Campos-Soria et al, 2011;Carvalho et al, 2014;Costa et al, 2017a,b;Doherty and Manfredi, 2001;Evangelia, 2014;Fungai Zengeni and Zengeni, 2013;Ng and Pine, 2003;Santero-Sanchez et al, 2015;Segovia-Pérez et al, 2019;Woods and Viehland, 2000). Moreover, gender discrimination is a cause of stress and turnover in kitchen occupations (Abdullah et al, 2009;Birdir and Canakci, 2014).…”
Section: Journal Articlesmentioning
confidence: 99%